Perceptions of Rheumatologists on Diagnosis of Psoriatic Arthritis in China - Miao Chen (Frontiers Media S.A., 2021)
ObjectiveHigh prevalence of undiagnosed psoriatic arthritis (PsA) and prolonged diagnostic delay are key troubles in the appropriate management of PsA. To analyze the possible causes for this phenomenon, a web-based nationwide survey was conducted to investigate rheumatologists’ perceptions on PsA diagnosis in China.MethodsThe electronic questionnaire consisting of 38 questions were designed by an expert panel and distributed with the online survey tool Sojump, which is a professional online survey platform. The completed questionnaires by real-name rheumatologists were collected.ResultsA total of 1594 valid questionnaires were included. More than half of Chinese rheumatologists reported it was challenging to make a diagnosis of PsA. The four major challenges were “Difficulties in identification of atypical or hidden psoriasis”, “Absence of diagnostic biomarkers”, “No active self-report of history or family history of psoriasis” and “Various musculoskeletal manifestations”. In diagnosing PsA, minor participants had incorrect knowledge of inflammatory arthropathy (13.7%), acute phase reactant (23.8%), and rheumatoid factor (28.7%). There were no significant differences in the knowledge of PsA and practice habits in diagnosing PsA between modern western medicine (WM)- and traditional Chinese medicine (TCM)-rheumatologists. The part-time rheumatologists were not as good as full-time rheumatologists in diagnosing PsA.ConclusionsAbout three quarters of Chinese rheumatologists are familiar with the elements in PsA diagnosis and have good practice habits in diagnosing PsA. Four main challenges in making PsA diagnosis are revealed. There was no significant difference in the knowledge of PsA between WM- and TCM-rheumatologists.